Testing a new seed-dressing fungicide formulation as an alternative to the banned chemicals - Bouanba, Fatima Zahra; El Miziani, Inaam; Kumari, Safaa (International Center for Agricultural Research in the Dry Areas, 2023)
Since 2018, the European Union and several other countries have decided to ban the sale and use of many pesticides containing thiram and thiamethoxam molecules, which led preventing shipments of seeds treated with these chemicals from entering these countries (Gautier, 2004). Accordingly, a new fungicide formulation should be sought as alternative to Celest top (thiamethoxam 262.5 g/l + fludioxonil 25 g/l + difenoconazole 25 g/l) and Vitavax (carboxin 200 g/l + thiram 200 g/l), which are the chemicals most commonly used as seed dressing to treat the seed-borne diseases. The common bunt is one of the most widespread seed-borne diseases and causes high losses in grain yield and quality. It is caused by two very closely related fungi, Tilletia tritici (syn. Tilletia caries) and T. laevis (syn. T. foetida) (Wilcoxson et al., 1996). The main objective of this research focuses on comparing the fungicide activity of a new formulation against the common bunt in wheat as well as their impact on crop growth and productivity.